HUBUNGAN PELAKSANAAN MANAJEMEN TERPADU BALITA SAKIT DENGAN KEPUASAN IBU BALITA SAKIT DI PUSKESMAS PANNAMBUNGAN KECAMATAN MARISO MAKASSAR - Yunita Gabriela Madu (Jurnal Keperawatan Florence Nightingale, 2019)
Management of Childhood Illness (IMCI) is a comprehensive program to handle the sick children who come to the Public Health Centre. Implementation of IMCI at Pannambungan Public Health Centre has not happened well because of the non-compliance with the health workers andinadequat the infrastructure. The specific goal of this research was to know the relationship implementation of Management of Childhood Illness (IMCI) with the satisfaction by mother's childhood illness at the Pannambungan Public Health Centre in Mariso Distric Makassar City. The study was an analytic observational using Cross Sectional Study. The population was all the mothers of childhood illness who get the IMCI service at the Pannambungan Public Health Centre and the most of the sample is 40 respondents using the Non Probability Sampling approach with Conscutive Sampling. Data collection by looking and observing the implementation of IMCI and the share satisfaction instrument. Data was analyzed by Chi Square test and alternative test to Fisher Exact Test because there was one cells expected count value is < 5 so the value p = 0,002 with means 5% (a= 0,05), so the value of p < a. It means that there was a relationship between implementation of Management of Childhood Illness (IMCI) with the satisfaction by mother of childhood illness at the Pannambungan Public Health Centre in Mariso Distric Makassar City. The study advices to all health workers to increase the IMCI service at the Public Health Center to good quality health service.